MIĘDZY TEORIĄ A PRAKTYKĄ – PRZEJAWY TEORII OSOBISTYCH W REFLEKSJI PRZYSZŁYCH NAUCZYCIELI JĘZYKA OBCEGO PODCZAS PRAKTYK PEDAGOGICZNYCH - Szymankiewicz, Krystyna (Neofilolog, 2019)
Teacher personal theories bridge a gap between theory and practice. Teacher training offers an opportunity for the trainee to become aware of their personal theories of practice and for these to be shaped . This article focuses on the role of reflection in the development of teacher personal theories of practice while training teachers of French as a foreign language. An interpretive analysis of messages posted on an Internet discussion forum for teacher trainees reveals how reflective students modify their personal theories on teaching by articulating theory and practice.